2013
DOI: 10.11604/pamj.2013.14.48.1973
|View full text |Cite
|
Sign up to set email alerts
|

Observance thérapeutique de l’hypertension artérielle et ses facteurs dans le service de cardiologie du CHU Tokoin de Lomé

Abstract: IntroductionEvaluer l’observance thérapeutique de l’HTA et de déterminer les facteurs de mauvaise observance chez les hypertendus au CHU Tokoin de Lomé.MéthodesNous avons effectué une étude transversale descriptive sur une durée de 6 mois en consultation externe dans le service de Cardiologie du CHU-Tokoin de Lomé. L’étude a concerné 363 patients hypertendus. L’évaluation de l’observance a été effectuée avec le test d’évaluation de l’observance de Girerd.RésultatsLe revenu mensuel était inférieur à 50.000 FCFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
10
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 0 publications
9
10
2
Order By: Relevance
“…The economic burden of these two diseases is difficult to determine but it appears that controlling them would be a good way to slow the onset of kidney failure in the population with heart failure [12]. Indeed, among our patients, the risk of developing renal failure was high with diabetes (RCa = 2.67) and much greater with hypertension [21]. These main etiologies also appear to be the main determinants of renal failure.…”
Section: Discussionmentioning
confidence: 77%
“…The economic burden of these two diseases is difficult to determine but it appears that controlling them would be a good way to slow the onset of kidney failure in the population with heart failure [12]. Indeed, among our patients, the risk of developing renal failure was high with diabetes (RCa = 2.67) and much greater with hypertension [21]. These main etiologies also appear to be the main determinants of renal failure.…”
Section: Discussionmentioning
confidence: 77%
“…According to Girerd X, et al [10], combinations of cardiovascular risk factors require patients to comply with up to ten prescription lines, thus reducing adherence. Machihude Pio, et al [19], found, 94.12% and 67.39% of patients who had respectively three or more tablets per day were poor observers; 76% and 58.16% of those who had three and two shots per day were also poor observers. C Konin, et al [14], found 77.3% of patients with more than three tablets a day and 95.3% of those who had three daily doses are worse observers.…”
Section: Factors Associated With Poor Adherencementioning
confidence: 96%
“…Better education could improve adherence to treatment, including diet and lifestyle measures, and reduce the cost of medical care. Studies have shown that, at different times, a good knowledge of hypertensive disease and medications was predictive of better adherence and better control of blood pressure [22,23]. Comorbidity can have a positive effect on adherence.…”
Section: Factors Associated With Poor Adherencementioning
confidence: 99%
“…Therapeutic data concerned current drugs for heart failure, side effect and compliance. The adherence to treatment was evaluated by Gired questionnaire [10]. Finally, quality of life was assessed by a validated tool: Minnesota Living with Heart Failure (MLHwFQ) which analyzes QOL during the last 4 weeks.…”
Section: Data Collectionmentioning
confidence: 99%